1991
DOI: 10.1007/bf00003921
|View full text |Cite
|
Sign up to set email alerts
|

Electron microscopy of human erythrocytes agglutinated by lectin from Codium fragile ssp. tomentosoides and pseudo-haemagglutinin from Ascophyllum nodosum

Abstract: Human erythrocytes were exposed to extracts of Codiumfragile ssp. tomentosoides, Ascophyllum nodosum, Dolichos biflorus seeds and a solution of purified polyphenols from Ascophyllum nodosum. In each case the erythrocytes appeared to agglutinate. Agglutinates were examined by scanning electron microscopy. Photomicrographs of the erythrocytes exposed to lectin-containing extracts of C. fragile and D. biflorus showed the typical appearance of agglutinated cells. Photomicrographs of the erythrocytes exposed to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
2
4
0
Order By: Relevance
“…However the polyphenols, are considered as pseudoagglutinating agents, since they do not cause haemagglutination but an agglomeration, by approaching the blood cells. This correlated with observations by Rogers and Wend Loveless (1991). 16 Under the conditions of this study, hemolytic activity was not observed in the blood groups tested; these observations may be related to the absence of saponins in the extracts.…”
Section: Results and Discussion:-supporting
confidence: 92%
See 1 more Smart Citation
“…However the polyphenols, are considered as pseudoagglutinating agents, since they do not cause haemagglutination but an agglomeration, by approaching the blood cells. This correlated with observations by Rogers and Wend Loveless (1991). 16 Under the conditions of this study, hemolytic activity was not observed in the blood groups tested; these observations may be related to the absence of saponins in the extracts.…”
Section: Results and Discussion:-supporting
confidence: 92%
“…This correlated with observations by Rogers and Wend Loveless (1991). 16 Under the conditions of this study, hemolytic activity was not observed in the blood groups tested; these observations may be related to the absence of saponins in the extracts. Similar results were described by other researchers, who reported only haemagglutinating activity for Amaranth extracts.…”
Section: Results and Discussion:-supporting
confidence: 92%
“…Furthermore, the presence of polyvinylpyrrolidone (which binds phenolic substances) in the buffer either eliminated the agglutination ability of the Dictyota dichotoma extract (for rabbit erythrocytes) or agglutination yielded non-reproducible results (Table 1). Rogers and Loveless (1991) have provided strong evidence that polyphenols in brown algal extracts cause agglutination of erythrocytes. Our data support this argument since phenolic binding polyvinylpyrrolidone inhibited agglutination by D. dichotoma extracts.…”
Section: Speciesmentioning
confidence: 98%
“…Over 60% of fiber is found in saltwort, which could perform as a crucial substance to control geriatric disease and could prevent the blood pressure rise and the colon cancer (4). Thus it is a useful marine plant that could be applied in the field of pharmacology and medicine and has the potential to be a candidate material for the treatment of hyperlipidemia as well as obesity (5).…”
Section: Introductionmentioning
confidence: 99%
“…So, interests in natural diet therapy have heightened as the physiological approach in lowering blood cholesterol level. Studies on the prevention and improvement of hyperlipidemia by applying functional materials extracted from natural food types are also generating widespread interest (5).…”
Section: Introductionmentioning
confidence: 99%